Landscape, Identity and Nation in the Postcolonial Caribbean: Edouard Glissant and Derek Walcott - Maglia, Graciela (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The role of landscape is central in Caribbean discourse; it overcomes the category of  décor consentant and emerges as an enérgeia that propels man into himself and into his self recognition. After the erosion of identity caused by the Atlantic crossing, the scission between subject and place caused by the middle passage and the negotiation of an in between space adapted to the New World, the Caribbean postcolonial cultural subject develops a transnational identity. An identity attached to the landscape and scenery, crossed by horizons, in a perpetual contraband of tongues, ethnic groups and borders. This identity has the certainty of belonging to a New World, which is constructs its nations beyond the monuments and documents inherited from the Empire. The Caribbean emerges as a rebellious wave that spills its water on new beaches of memory. The poetics of the Caribbean build Nation from the imagination, as Derek Walcott proposes. On the other hand, Edouard Glissant speaks about une poétique de la relation in the Caribbean, a poetic of exuberance and ecstasies, a poetical outcome for the shipwrecked. The analysis of these unpreced ented imaginaries will take us from Literary Studies to Anthropology, Ethnography and Cultural Studies.